The Relevance of Accounting Information Value and the Portion of Non Public Ownership in Investment Decision Making - Sahninda, Berian Putra; Pujiono, Pujiono (Amsir Accounting & Finance Journal, 2025)
The purpose of this research is to analyze the effect of the relevance of the value of accounting information which includes Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Non Public Ownership (KNP) in making investment decisions. The research method used is quantitative method with 15 companies in the agriculture industry sector as the sample. This research uses multiple linear regression techniques as hypothesis testing. The results of the research show that ROA, EPS and Non-Public Ownership are proven to have an effect on the fluctuation of stock prices, while ROE is proven to have no effect on stock prices. The implication of this research is the importance of looking at the size of the KNP and the relevant value of accounting information in the forms of ROA and EPS while still considering the risks associated with the value of ROE in the investment decision-making process